(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article analyze situation of govermental debt in Uzbekistan and some countries. In the article are given some solutions to this problem such as Islamic fianancing instruments and public-private partnerships